2015
DOI: 10.1002/tcr.201402097
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Structure of Membrane Lipids and Natural Products Elucidated by a Chemistry‐Based Approach

Abstract: Determining the bioactive structure of membrane lipids is a new concept, which aims to examine the functions of lipids with respect to their three-dimensional structures. As lipids are dynamic by nature, their "structure" does not refer solely to a static picture but also to the local and global motions of the lipid molecules. We consider that interactions with lipids, which are completely defined by their structures, are controlled by the chemical, functional, and conformational matching between lipids and be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 87 publications
0
13
0
Order By: Relevance
“…However, the domain formation at the nanometer scale, one of the major topics in this study, could not be visualized with the spatial resolution of these microscopic images. We thus became interested in FRET experiments because SM in the Lo phase is prone to form gel-like domains with nanometer size ( 7 , 23 , 24 , 25 , 28 , 33 ). Using this approach, we examined the possibility that SSM-SSM and ent- SSM- ent- SSM interactions caused the segregation of the SSM and ent -SSM nano-subdomains within the Lo domains of various membrane systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the domain formation at the nanometer scale, one of the major topics in this study, could not be visualized with the spatial resolution of these microscopic images. We thus became interested in FRET experiments because SM in the Lo phase is prone to form gel-like domains with nanometer size ( 7 , 23 , 24 , 25 , 28 , 33 ). Using this approach, we examined the possibility that SSM-SSM and ent- SSM- ent- SSM interactions caused the segregation of the SSM and ent -SSM nano-subdomains within the Lo domains of various membrane systems.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the homophilic interactions between SSM and SSM through the amide (or hydroxy) group appeared to be a leading cause of the nanodomain formation of SSM (or ent -SSM). The ordering effect of Cho was comparable for SSM and ent -SSM, indicating that Cho does not strongly interact with the polar group of SMs bearing the chiral centers, instead largely interacting with the SM alkyl chains ( 11 , 28 , 33 ).…”
Section: Introductionmentioning
confidence: 97%
“…Lipid membranes comprising chiral lipids are expected to serve as a chiral environment for the transformation of asymmetric compounds by chemical and enzymatic reactions, which may occur in biological membranes. Organic synthesis for preparing stereoisomers of lipids and physicochemical methodologies for examining their interactions are indispensable to make the best use of chirality of lipids in chemistry‐ and biophysics‐based research of biological membranes.…”
Section: Resultsmentioning
confidence: 99%
“…12 More recently, confocal fluorescence microscopy has disclosed that TNM-A permeabilizes the membrane by altering the membrane morphology; this effect significantly occurs only in Chol-containing liposomes. 18 However, it remains unclear how the interaction of TNM-A with membranes leads to the uneven membrane curvature, and what role…”
Section: Membrane Penetration Of Tnm-a Examined By 1 H Nmr Paramagnetmentioning
confidence: 99%